2008
DOI: 10.1080/00016340801899347
|View full text |Cite
|
Sign up to set email alerts
|

Association between a Mediterranean‐type diet and risk of preterm birth among Danish women: a prospective cohort study

Abstract: Shifting towards a MD during pregnancy may reduce the risk of early delivery in Danish women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(156 citation statements)
references
References 28 publications
(35 reference statements)
5
145
1
2
Order By: Relevance
“…We examined the abstracts of these publications and their reference lists and found 36 potentially eligible manuscripts. Detailed review of these for inclusion and exclusion criteria ( Figure 1) yielded a total of 22 epidemiologic studies, including 15 cohort studies (8,9,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)) and 7 case-control studies (26,(42)(43)(44)(45)(46)(47) (Tables 1 and 2). One of the case-control studies (47) reported effect estimates for both coffee and caffeinated soda consumption.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the abstracts of these publications and their reference lists and found 36 potentially eligible manuscripts. Detailed review of these for inclusion and exclusion criteria ( Figure 1) yielded a total of 22 epidemiologic studies, including 15 cohort studies (8,9,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)) and 7 case-control studies (26,(42)(43)(44)(45)(46)(47) (Tables 1 and 2). One of the case-control studies (47) reported effect estimates for both coffee and caffeinated soda consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled estimate of relative risk from linear dose-response meta-analysis was 1.02 (95% CI: 0.98 to 1.06) per 100 mg/day of caffeine (P = .42) (figure 2E). Of the five studies that could not be included in meta-analyses, four suggested some positive association [40][41][42][43], and one did not [44].…”
Section: Preterm Deliverymentioning
confidence: 99%
“…(yes, no). Most of these variables have been described and used in earlier studies based on the DNBC (31)(32)(33)(34)(35)(36)(37)(38)(39)(40) .…”
Section: Assessment Of Dietary Patternsmentioning
confidence: 99%